PROTEIN (CIEP) AND ORGANIC (FTIR) RESIDUE ANALYSIS OF SEDIMENT FROM THE PRINCE OF WALES NATIONAL HISTORIC SITE (PWF), IeKn-24, HUDSON BAY COUNTY, MANITOBA, CANADA - Scott Cummings, Linda (PaleoResearch Institute); Milligan, Jennifer L.B. (PaleoResearch Institute) (the Digital Archaeological Record)
In 1730, the Hudson’s Bay Company initiated the development of the Prince of Wales Fort II on Eskimo Point at the mouth of Churchill River and the Hudson Bay in northern Manitoba, Canada. Construction of the stone fortification took over 40 years, during which Hudson’s Bay Company employees, including officers, tradesmen, and laborers, were present at the site. Activities at the fort included tasks related to survival (hunting, cutting wood, hauling water, etc.) and fur trading. The fort’s northern location offered trade access with First Nations Peoples including the Dene (Chipewyan), Inuit, and Cree (Parks Canada 2011). Overall the fort was occupied between approximately 1731 and 1782 (Donalee Deck, personal communication November 10, 2010). “Greasy” sediments found adjacent to a leather bag were among the archaeological discoveries made during investigations in the southwest bastion rampart of the fort (Donalee Deck, personal communication February 26, 2016). Protein residue and organic residue analyses were employed to help identify the “greasy” aspect of the sediment.